The roles of linguistic confidence and integrative motivation on cross-cultural adaptation of Asian degree students Finland - Nguyen Thi Thanh, Thao (2015)
While cross-cultural adaptation of international students has become more and more popular topics in the field of intercultural communication, there are few studies related to students who come to non-native-English-speaking countries to study international programs. Specifically, the number of Asian students enrolling in international degree programs in Finland has been increasing recently. Besides other difficulties, language has become one of the most baffling issues in the process of both sociocultural adaptation and psychological adaptation of strangers in the host country (Maza, 1963). By narrowing the impacts of integrative motivation and linguistic confidence, they have drawn some results in cross-cultural adaptation of Asian degree students in Finland. This research may address both advantages and disadvantages of language matters. Although international students study in English in Finland, they have to know some basic Finnish or even Swedish while living in Finland. Hence, this leads to some interesting findings in this particular context. A quantitative research method was conducted in this paper in order to test hypotheses and explore research question through numerical data. On the other hand, the research survey was circulated in many regions of Finland by means of e-mails and social network. The data were analyzed by using Pearson correlation coefficient and simple regression analysis with the support of SPSS software. Basically, the results of this study illustrate the roles of integrative motivation and linguistic confidence, which include both English language and host language, in the process of cross-cultural adaptation of Asian degree students in Finland. This study has profound implications for future research and may help solve the problems related to language issues of students who choose to study international programs in non-native-English-speaking countries. In conclusion, this research sheds new light on little acknowledged roles of integrative motivation and linguistic confidence on cross-cultural adaptation of Asian degree students in Finland.